COMPATIBILITY OF CHARACTERISTIC OF HYDROLIC RAM PUMP AND RAIN HARVEST TECHNOLOGY WITH LOCAL CHARACTERISTICS IN ENDE REGENCY, EAST NUSA TENGGARA - Made Widiadnyana Wardiha; Pradwi Sukma Ayu Putri; Iwan Suprijanto (Widyariset, 2012)
A study about compatibility of characteristic of hydraulic rams (hidram) pump and rain harvest with localcharacteristics (location and society) in Ende Regency, East Nusa Tenggara, has been done. Data includingsecondary data such as characteristic of hidram pump and rain harvest, and primary data from questionnaire.The respondent are from stakeholders in Ende Regency such as public works department, regional company forwater supply (PDAM), regional agency for development planning (Bappeda), and water supply consultant. Dataanalysis was using descriptive analysis. Compatibility of technology application is seen in the aspect of needs,society empowerment, energy saving, cost, social, and cultural at Ende Regency. The study result showed thathidram pump technology compatible to be applied in Ende but needs to be studied about material standard andmodification for increasing efficiency of hidram pump. Rain harvest technology can be applied at Ende but need amodification about disinfection and filtering process before consumed.